PERAN LEMBAGA AMIL ZAKAT, INFAK, DAN SEDEKAH NAHDLATUL ULAMA (LAZISNU) DALAM PENGELOLAAN ZIS DI KOTA MANADO - Amiruddin, Amiruddin; Gia, Zulkaina; Dunggio, Nahdia (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
This study examines the management of Zakat, Infaq, and Sadaqah (ZIS) at the Amil Zakat, Infaq, and Sadaqah Institution of Nahdlatul Ulama (LAZISNU) in the city of Manado. This research uses a qualitative method with observation and in-depth interview techniques. The results show that LAZISNU has implemented various social programs such as education, disaster response, health, and economic empowerment. LAZISNU has adopted digital systems such as QRIS for the collection of zakat, infaq, and sadaqah, and its transparent financial reporting has helped build public trust. However, there are still some challenges, including the incomplete empowerment programs for mustahik (zakat recipients) and the limited operational office facilities. This study recommends enhancing zakat education and strengthening inter-institutional collaboration to improve the effectiveness of ZIS fund distribution. Penelitian ini mengkaji tentang pengelolaan Zakat, Infak, dan Sedekah ( ZIS ) di Lembaga Amil Zakat, Infaq, dan Sedekah Nahdlatul Ulama ( LAZISNU ) di Kota Manado. Penelitian ini menggunakan metode kualitatif dengan teknik observasi dan wawancara mendalam. Hasilnya menujukan bahwa LAZISNU telah melaksanakan program-program sosial seperti pendidikan, tanggap bencana, kesehatan, dan ekonomi. LAZISNU telah menggunakan sistem digital seperti Qris dalam hal pengumpulan zakat, infak, maupun sedekah, serta pelaporan keuangan yang transparan telah memperkuat kepercayaan publik. Akan tetapi, masih terdapat beberapa tantangan mulai belum sempurnanya program pemberdayaan mustahik dan keterbatasan kantor operasional. Penelitian ini merekomendasikan perlunya peningkatan edukasi zakat dan penguatan kolaborasi antar lembaga untuk meningkatkan efektivitas distribusi dana ZIS.